1974
DOI: 10.1177/0013161x7401000102
|View full text |Cite
|
Sign up to set email alerts
|

Reward Structures in the Public High School

Abstract: This study examines the relationship between eight categories of rewards available to teachers in high schools and teacher behaviors of absenteeism, recruitment and retention. Findings emphasize the importance of intrinsic motivators in professional organizations and suggest basic differences in motivational patterns between professional and production oriented organizations. Dennis W. Spuck is an Assistant Professor of Educational Administration at the University of Wisconsin-Madison. Educational instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Older studies (Garbarino, 1975;McLaughlin and Marsh, 1978;Spuck, 1974) have indicated that although financial incentives can promote specific behaviors (such as accepting difficult teaching assignments) and direct teachers' efforts toward measurable goals (such as achieving higher test scores among their pupils), they are less promising as tools to improve general teaching performance (Moore, 1986). There seems to be extensive evidence that teachers regard professional efficacy, not money, as the primary motivator in their work (Scott, Cox, and Dinham, 1999;Dierynck and others, 1998;Garbarino, 1975;McLaughlin and Marsh, 1978;Spuck, 1974).…”
Section: S C H E P E R S De Gieter Pepermans Du Bois Caers Jegersmentioning
confidence: 99%
See 1 more Smart Citation
“…Older studies (Garbarino, 1975;McLaughlin and Marsh, 1978;Spuck, 1974) have indicated that although financial incentives can promote specific behaviors (such as accepting difficult teaching assignments) and direct teachers' efforts toward measurable goals (such as achieving higher test scores among their pupils), they are less promising as tools to improve general teaching performance (Moore, 1986). There seems to be extensive evidence that teachers regard professional efficacy, not money, as the primary motivator in their work (Scott, Cox, and Dinham, 1999;Dierynck and others, 1998;Garbarino, 1975;McLaughlin and Marsh, 1978;Spuck, 1974).…”
Section: S C H E P E R S De Gieter Pepermans Du Bois Caers Jegersmentioning
confidence: 99%
“…There seems to be extensive evidence that teachers regard professional efficacy, not money, as the primary motivator in their work (Scott, Cox, and Dinham, 1999;Dierynck and others, 1998;Garbarino, 1975;McLaughlin and Marsh, 1978;Spuck, 1974). There is even some evidence that the prospect of extrinsic rewards may diminish the potential of intrinsic rewards (Moore, 1986).…”
Section: S C H E P E R S De Gieter Pepermans Du Bois Caers Jegersmentioning
confidence: 99%
“…Johnson (1986) notes that both extrinsic rewards, such as pay and promotion, as well as intrinsic rewards, such as pride in work, can supply motivation for teachers. Following the lead of Spuck (1974), she contends that better pay and higher status might draw those with an interest in teaching to the profession, but probably are not sufficient to retain or sustain outstanding staff members, as the best teachers stay in teaching because of intrinsic rewards. According to Goodlad (1984):…”
Section: Work Satisfaction In Teachingmentioning
confidence: 99%
“…Ainsi, par exemple, Sergiovanni (1967) a établi que les facteurs intrinsèques au travail étaient une source de satisfaction des ensei gnants. Spuck (1974), pour sa part, a trouvé que les récompenses intrinsèques étaient reliées au rendement au travail des enseignants, à une réduction de leur absentéisme et à l'efficacité de leur comportement en classe. Enfin, Toupin, Les sard, Cormier et Valois (1982) ont montré que les enseignants du Québec, d'une façon générale, sont «plutôt» ou «assez» satisfaits à l'égard de certaines dimen sions intrinsèques de leur travail.…”
Section: Les Bases Théoriques De L'étudeunclassified